-9/x=-x / 4/49
CẦN GẤP
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{9}{2}\) \(-\) ( \(x\) \(-\) \(\frac{3}{4}\) ) = \(\frac{25}{4}\)
\(x\) \(-\) \(\frac{3}{4}\) = \(\frac{9}{2}\) \(-\) \(\frac{25}{4}\)
\(x\) \(-\) \(\frac{3}{4}\) = \(-\frac{7}{4}\)
\(x\) = \(-\frac{7}{4}\) \(+\) \(\frac{3}{4}\)
\(x\) = \(-1\)
\(4\) \(+\) \(x\) \(+\) \(\frac{3}{4}\) = \(\frac{17}{2}\)
( \(4\) \(+\) \(\frac{3}{4}\)) \(+\)\(x\) = \(\frac{17}{2}\)
\(\frac{19}{4}\) \(+\) \(x\) = \(\frac{17}{2}\)
\(x\) = \(\frac{17}{2}\) \(-\) \(\frac{19}{4}\)
\(x\) = \(\frac{15}{4}\)
c: Ta có: \(\left(2x-3\right)^2-\left(2x-3\right)\left(x-10\right)=7\)
\(\Leftrightarrow4x^2-12x+9-2x^2+20x+3x-30=7\)
\(\Leftrightarrow11x=28\)
hay \(x=\dfrac{28}{11}\)
d: Ta có: \(\left(3x-4\right)^2-9\left(x-3\right)\left(x+3\right)=8\)
\(\Leftrightarrow9x^2-24x+16-9x^2+81=8\)
\(\Leftrightarrow-24x=-89\)
hay \(x=\dfrac{89}{24}\)
f: Ta có: \(\left(x+4\right)^2-\left(x+1\right)\left(x-1\right)=16\)
\(\Leftrightarrow x^2+8x+16-x^2+1=16\)
\(\Leftrightarrow8x=-1\)
hay \(x=-\dfrac{1}{8}\)
(Tớ sửa lại đề nhé.)
\(\dfrac{x-5}{x^2-9}-\dfrac{5}{3-x}=\dfrac{4}{x+3}\)
Điều kiện: \(x\ne\pm3\)
\(\Leftrightarrow\dfrac{x-5}{\left(x+3\right)\left(x-3\right)}+\dfrac{5\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}=\dfrac{4\left(x-3\right)}{\left(x+3\right)\left(x-3\right)}\)
\(\Rightarrow x-5+5x+15=4x-12\)
\(\Leftrightarrow x+5x-4x=-12-15+5\)
\(\Leftrightarrow2x=-22\)
\(\Leftrightarrow x=-11\)
a) \(9\left(x-1\right)^2-\frac{4}{9}\div\frac{2}{9}=\frac{1}{4}\)
\(\Leftrightarrow9\left(x-1\right)^2-2=\frac{1}{4}\)
\(\Leftrightarrow9\left(x-1\right)^2=\frac{9}{4}\)
\(\Leftrightarrow\left(x-1\right)^2=\frac{1}{4}\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=\frac{1}{2}\\x-1=-\frac{1}{2}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{3}{2}\\x=\frac{1}{2}\end{cases}}\)
b) \(\left(3x-1\right)^6=\left(3x-1\right)^4\)
\(\Leftrightarrow\left(3x-1\right)^6-\left(3x-1\right)^4=0\)
\(\Leftrightarrow\left(3x-1\right)^4\cdot\left[\left(3x-1\right)^2-1\right]=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(3x-1\right)^4=0\\\left(3x-1\right)^2=1\end{cases}}\Leftrightarrow x\in\left\{0;\frac{1}{3};\frac{2}{3}\right\}\)
TL
x =\(\pm\)42
HT